2018
DOI: 10.1111/cns.13062
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and FK506 derivative TH2849 could ameliorate neurodegenerative diseases through autophagy with low immunosuppressive effect

Abstract: Summary Autophagy is an essential cellular process concern with cellular homeostasis down‐regulated by mTOR, whose activity can be modulated by rapamycin, a kind of lipophilic macrolide antibiotic, through forming a complex with immunophilin FKBP12 essential for mTOR regulation to induce autophagy. Therefore, rapamycin is normally used as a neuron protective agent. The immunophilin FKBP12 binding ligand FK506 is well known as an immunosuppressive agent by inhibiting the calcineurin expression. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Autophagy enhancers that can be utilized for the potential treatment of neurodegenerative diseases is receiving growing attention in recent studies [9,18,93,94]. It has been shown that the inactivation of mTOR by the lipophilic macrolide antibiotic rapamycin promotes the induction of autophagy [95]. Furthermore, long-term administration of rapamycin can reduce amyloid load in mouse models of AD and improve cognitive function as well as the pathology of tauopathy [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy enhancers that can be utilized for the potential treatment of neurodegenerative diseases is receiving growing attention in recent studies [9,18,93,94]. It has been shown that the inactivation of mTOR by the lipophilic macrolide antibiotic rapamycin promotes the induction of autophagy [95]. Furthermore, long-term administration of rapamycin can reduce amyloid load in mouse models of AD and improve cognitive function as well as the pathology of tauopathy [96,97].…”
Section: Discussionmentioning
confidence: 99%
“…The specific mTORC1 inhibitor, rapamycin, and its derivatives (rapalogs) demonstrated to alleviate neuropathology and neurodegeneration in several transgenic models of pathogenic proteins, including models of HD (mutant HTT) ( Ravikumar et al., 2004 ; Sarkar and Rubinsztein, 2008 ), AD (mutant APP) ( Spilman et al., 2010 ; Caccamo et al., 2010 ), SCA type 3 ( Menzies et al., 2010 ), and PD (mutant α-synuclein) ( Webb et al., 2003 ). Rapamycin decreases neuronal death in MPTP-mediated PD animal models ( Ding et al., 2019 ; Liu et al., 2013a ). Furthermore, rapamycin diminishes muHTT fragments toxicity in cellular and mice models ( Ravikumar et al., 2004 ).…”
Section: Use Of Autophagy Modulators For Neurogenerative Disordersmentioning
confidence: 99%
“…In another mouse model with the expression of a mutated APP, long-term rapamycin treatment decreases Aβ levels and alleviates the AD phenotype ( Spilman et al., 2010 ). Likewise, beneficial effects over neurodegeneration are observed with new rapalog compounds such as TH2849 which is an FKBP12-FK506 derivative ( Ding et al., 2019 ). Despite the promissory results of rapamycin and rapalogs, they cannot be generalized to all neurodegenerative diseases since mixed data are obtained for ALS.…”
Section: Use Of Autophagy Modulators For Neurogenerative Disordersmentioning
confidence: 99%
“…So it is necessary to use neuroprotective drugs additionally. Calcineurin inhibitor (tacrolimus, FK506), the most effective neuroprotective drug in central nervous system diseases, can maintain intracellular calcium homeostasis to improve neuronal repair and regeneration 21 , 22 , 23 , 24 , 25 , 26 . Moreover, the amelioration of AD-like behavior has been observed in patients taking FK506 21 , 24 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Calcineurin inhibitor (tacrolimus, FK506), the most effective neuroprotective drug in central nervous system diseases, can maintain intracellular calcium homeostasis to improve neuronal repair and regeneration 21 , 22 , 23 , 24 , 25 , 26 . Moreover, the amelioration of AD-like behavior has been observed in patients taking FK506 21 , 24 , 26 . To sum up, we combined ibuprofen and FK506 for AD treatment, which could not only inhibit neuroinflammation mediated by NF- κ B pathway, but also exert neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%